2019
DOI: 10.1038/s41566-019-0477-4
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low excess noise and high sensitivity AlAs0.56Sb0.44 avalanche photodiodes

Abstract: Fast, sensitive avalanche photodiodes (APDs) are required for applications such as high-speed data communications and light detection and ranging (LIDAR) systems. Unfortunately the InP and InAlAs used at the gain material in these APDs have similar electron and hole impact ionisation coefficients (α and β respectively) at high electric fields, giving rise to relatively high excess noise, limiting their sensitivity and gain bandwidth product (GBP) 1. Here, we report on extremely low excess noise in AlAs0.56Sb0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 30 publications
4
48
0
Order By: Relevance
“…Hole impact ionization is also likely to be suppressed due to the flattening of the heavy hole band as aluminum content increases [29], which may cause the interband scattering rate to increase and prevent holes from accumulating sufficient energy to impact ionize [30]. It is notable that AlAs 0.56 Sb 0.44 , Al 0.85 Ga 0.15 As 0.56 Sb 0.44 , and Al x In 1−x As y Sb 1−y , all of which have recently been reported to have very low β/α ratios [12], [13], [31] are also indirect bandgap semiconductors with the lowest conduction band edge in the X valley.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hole impact ionization is also likely to be suppressed due to the flattening of the heavy hole band as aluminum content increases [29], which may cause the interband scattering rate to increase and prevent holes from accumulating sufficient energy to impact ionize [30]. It is notable that AlAs 0.56 Sb 0.44 , Al 0.85 Ga 0.15 As 0.56 Sb 0.44 , and Al x In 1−x As y Sb 1−y , all of which have recently been reported to have very low β/α ratios [12], [13], [31] are also indirect bandgap semiconductors with the lowest conduction band edge in the X valley.…”
Section: Discussionmentioning
confidence: 99%
“…There is also interest in GaAs-based SAM-APDs with wide bandgap multiplication regions, using GaNAsSb and GaSb absorption regions for SWIR detection [10], [11]. The understanding gained from this alloy system may also be useful in determining the optimum compositions of other Al/Ga containing alloy systems such as Al x Ga 1−x As 0.56 Sb 0.44 , for which extremely low-noise APDs have been recently reported [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…We previously modelled the performance of 30 μm diameter InGaAs-AlAsSb based SAM-APDs [30] where we showed that it was possible to achieve a sensitivity of -32.1 dBm at BER=10 -12 at 1550 nm for a 10 Gb/s optical system. The prediction there assumed an InGaAs absorption region that is 600 nm thick with a maximized-induced current (MIC) design [31] and capable of a unity gain responsivity of 0.92 A/W.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Thick AlAs 0.56 Sb 0.44 APDs on InP substrates have also been successfully grown as AlAs/ AlSb SLs for a 1550 nm thick M-layer. The SLs exhibited an extremely low k-value of 0.005 16 . To investigate the origin of lower k-value in a SL APD, AlAs/InAs SL (compositionally the same as Al 0.48 In 0.52 As RA) APDs were grown on an InP substrate.…”
mentioning
confidence: 99%
“…However, an APD technology at least needs to be comparable to Si APDs, and the AlGaAsSb APDs cannot achieve such a low k-value with relatively thin layers. A way to attain the low k-value is to have an M-layer that is ~ 1500 nm thick 16 . Unfortunately, AlGaAsSb APDs cannot be randomly grown with such large thicknesses due to the existence of a large miscibility gap, causing phase separation during the growth.…”
mentioning
confidence: 99%